Neurocognitive Disorders and Dehydration in Older Patients: Clinical Experience Supports the Hydromolecular Hypothesis of Dementia - Lauriola, Michele; Mangiacotti, Antonio; D’Onofrio, Grazia; Cascavilla, Leandro; Paris, Francesco; Paroni, Giulia; Seripa, Davide; Greco, Antonio; Sancarlo, Daniele (Nutrients, 2018)
Abnormalities of water homeostasis can be early expressions of neuronal dysfunction, brain atrophy, chronic cerebrovasculopathy and neurodegenerative disease. The aim of this study was to analyze the serum osmolality of subjects with cognitive impairment. One thousand and ninety-one consecutive patients attending the Alzheimer’s Evaluation Unit were evaluated with the Mini-Mental State Examination (MMSE), 21-Item Hamilton Depression Rating Scale (HDRS-21), Activities of Daily Living (ADL), Instrumental-ADL (IADL), Mini Nutritional Assessment (MNA), Exton-Smith Scale (ESS), and Cumulative Illness Rating Scale (CIRS). For each patient, the equation for serum osmolality developed by Khajuria and Krahn was applied. Five hundred and seventy-one patients had cognitive decline and/or depression mood (CD-DM) and 520 did not have CD-DM (control group). Patients with CD-DM were less likely to be male (p < 0.001), and were more likely to be older (p < 0.001), have a significant clear cognitive impairment (MMSE: p < 0.001), show the presence of a depressive mood (HDRS-21: p < 0.001) and have major impairments in ADL (p < 0.001), IADL (p < 0.001), MNA (p < 0.001), and ESS (p < 0.001), compared to the control group. CD-DM patients had a higher electrolyte concentration (Na+: p < 0.001; K+: p < 0.001; Cl−: p < 0.001), risk of dehydration (osmolality p < 0.001), and kidney damage (eGFR: p = 0.021), than the control group. Alzheimer’s disease (AD) patients showed a major risk for current dehydration (p ≤ 0.001), and dehydration was associated with the risk of developing a type of dementia, like AD or vascular dementia (VaD) (OR = 2.016, p < 0.001). In the multivariate analysis, the presence of dehydration state was associated with ADL (p < 0.001) and IADL (p < 0.001), but independently associated with age (r2 = 0.0046, p = 0.77), ESS (r2 = 0.0052, p = 0.54) and MNA (r2 = 0.0004, p = 0.48). Moreover, younger patients with dementia were significantly more dehydrated than patients without dementia (65–75 years, p = 0.001; 76–85 years, p = 0.001; ≥86 years, p = 0.293). The hydromolecular hypothesis intends to explain the relationship between dehydration and cognitive impairment in older patients as the result of protein misfolding and aggregation, in the presence of a low interstitial fluid volume, which is a defect of the microcirculation. Defective proteins were shown to impair the amount of information in brain biomolecular mechanisms, with consequent neuronal and synaptic damage.